PENGARUH HAND MASSAGE TERHADAP TINGKAT KECEMASAN PASIEN PRE OPERASI PADA PEMBEDAHAN ELEKTIF - Azizatul Baderiyah; Joko Pitoyo; Anggun Setyarini (Poltekkes Kemenkes Malang, 2021)
More patients who will do a surgical procedure need a special handling to keep the stability of condition before doing the procedure. Usully the patients before were done to surgery, they feel anxiety which can risk causing problems and can cause problem eventually that can influence the process of the operation and can make delay of surgery. This study was conducted to determine the effect of hand massage on the anxiety level of preoperative patients in elective surgery. This study uses a literature review method with a research strategy using the PICOS framework. Then selected using the PRISMA diagram so that eight journals were obtained. Journals are drawn from the ScienceDirect, Pubmed and Google scholar databases. Assessment of the quality of the eight articles using JBI Critical Appraisal tools then the journals were analyzed one by one, summaries were made, similarities and differences were sought, researches that supported each other, research that contradicted each other, and then conducted a discussion to draw conclusions. The data are presented in the form of narratives and tables. The results of the study mostly used the Randomized Control Trial design, the sample was over 80 respondents, 4 studies in Iran, 2 studies in the USA, 1 study in Turkey, and 1 study in China. Preoperative patients who are waiting for surgery, 4 types of surgery are; general surgary, eye, heart, and ambulation operations, the average number of respondents is 50-100 individuals, the average age is 41 to 66 years, the majority of respondents felt moderate preoperative anxiety. The conclusion of the study showed that there was an effect of hand massage on the anxiety level of preoperative patients in elective surgery. The level of anxiety in patients who will doing surgery can decrease with supportive support for themselves, one of them is through hand massage. Keywords : Hand Massage, Pre Operative Elective, Anxiety